2020
DOI: 10.1001/jamapsychiatry.2019.4815
|View full text |Cite|
|
Sign up to set email alerts
|

Individual Differences in Response to Antidepressants

Abstract: IMPORTANCE Antidepressants are commonly used worldwide to treat major depressive disorder. Symptomatic response to antidepressants can vary depending on differences between individuals; however, this variability may reflect nonspecific or random factors.OBJECTIVES To investigate the assumption of systematic variability in symptomatic response to antidepressants and to assess whether this variability is associated with severity of major depressive disorder, antidepressant class, or year of study publication.DAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 99 publications
0
29
0
Order By: Relevance
“…It is important to note that a VR (or CVR) sufficiently smaller than 1 is in fact evidence of relevant treatment effect heterogeneity (see supplementary figure 8 and 9). Therefore, considering the lnCVR as the main outcome would lead to the opposite conclusion of substantial treatment effect heterogeneity [36].…”
Section: Methodological Aspectsmentioning
confidence: 99%
“…It is important to note that a VR (or CVR) sufficiently smaller than 1 is in fact evidence of relevant treatment effect heterogeneity (see supplementary figure 8 and 9). Therefore, considering the lnCVR as the main outcome would lead to the opposite conclusion of substantial treatment effect heterogeneity [36].…”
Section: Methodological Aspectsmentioning
confidence: 99%
“…Several analyses of variability based on study-level data, however, found no evidence of greater variability in the active treatment arm, and thus concluded that treatment effects are likely to be relatively constant, which suggests the scope for personalisation of treatment is limited (7)(8)(9)(10)(11)(12)(13). These findings were surprising given the widespread clinical belief that patients differ substantially in their response to medication.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analysis of variability has recently become an area of intense interest in psychiatric research. The technique has been applied to understand variability of brain structure (1), and subsequently brain function (2)(3)(4)(5), immune function (6), and more recently to investigate variability in randomised controlled trials (RCTs) of therapeutic interventions thereby potentially providing an estimate of treatment effect heterogeneity (7)(8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Response rates to standard first-line treatment such as antidepressant medication in MDD patients are modest ranging from 30-50% only [3,4]. Failure to identify the widely suspected distinct clinical and neurobiological subtypes underlying depression heterogeneity and subsequent inability to account for differing subtypes via appropriate treatment stratification is thought to represent a major cause of modest treatment success [5][6][7][8][9]. Recent psychiatric research aims to overcome this obstacle by studying depression heterogeneity and has consistently highlighted the relevance of atypical features of depression.…”
Section: Introductionmentioning
confidence: 99%